A new Middle Triassic (Ladinian) trilophosaurid stem-archosaur from Germany increases diversity and temporal range of this clade. Issue 3 (22nd March 2023) - Sues, Hans-Dieter; Schoch, Rainer R.
Abstract : We report the first trilophosaurid stem-archosaur from Central Europe, Rutiotomodon tytthos gen. et sp. nov., from the Middle Triassic (Ladinian) Erfurt Formation of Baden-Württemberg (Germany). It is currently known from two jaw fragments with distinctive teeth. The labiolingually wide but mesiodistally narrow maxillary and dentary teeth each have a large labial cusp from which an occlusal ridge extends lingually to a small lingual cusp. A mesial and a distal cingulum extend between the labial and lingual cusps. The mesial and distal faces of the labial cusp each bear three prominent, lingually curved apicobasal ridges (arrises). A referred partial dentary has an edentulous, expanded symphysis similar to the mandibular 'beak' in Trilophosaurus buettneri . A review of Coelodontognathus ricovi, from the Lower Triassic (Olenekian) of southwestern Russia, supports its referral to Trilophosauridae rather than Procolophonidae. Based on this reassessment and the new material from the Middle Triassic, the temporal range of trilophosaurids now spans nearly the entire Triassic Period, from the Olenekian to the Rhaetian. Trilophosaurids present craniodental features that indicate omnivory or herbivory with limited oral food processing. They were more diverse in terms of dental structure (and presumably diet) than previously assumed.